Burden of Anemia among Human Immunodeficiency Virus-Positive Adults on Highly Active Antiretroviral Therapy at Hawassa University Compressive Specialized Hospital, Hawassa, Ethiopia - Sisay Tesfaye; Melaku Hirigo; Dawit Jember; Mekdes Shifeta; Worku Ketema (Anemia)
Background. Anemia is the most common hematologic abnormality associated with human immunodeficiency virus (HIV)-infected patients and affects 60% to 80% of patients in late-stage disease. It has a considerable impact on the progression of HIV to advanced stages. This study aimed at assessing the burden of anemia in adult HIV-infected patients who are on highly active antiretroviral therapy (HAART) and have follow-up at Hawassa University Comprehensive Specialized Hospital (HUCSH) Antiretroviral therapy (ART) clinic. Methods. A hospital-based retrospective study was conducted among HIV-positive adults on HAART at Hawassa University Compressive Specialized Hospital. The systematic sampling method was used to choose a total of 244 study participants. Data on demographic characteristics, related factors of anemia, latest hemoglobin, CD4, and ART regimens were collected using a structured data abstraction format. The data were cleaned and analyzed using SPSS version 21.0 after being manually checked for completeness. Multivariable logistic regression was carried out to detect elements associated with anemia. A P value of <0.05 was used as a cutoff point to announce statistical significance. Results. The records of 244 patients were examined in total. Anemia was present in 29.9% (95% CI 23.8–35.2) among adult HIV patients. Female sex (AOR: 2.576, 95% (CI: 1.295–5.127)), having tuberculosis (TB) (AOR: 4.873, 95% (CI: 1.534–15.484)), taking a zidovudine (ZDV)-containing ART regimen (AOR: 5.216, 95% (CI: 1.239–21.962)), having clinical WHO stage IV and III diseases (AOR: 3.077, 95% CI (1.244–7.612)), having body mass index (BMI) <18.5 kg/m2 (AOR: 2.391, 95% (CI: 1.138–5.023)), and taking cotrimoxazole prophylaxis (AOR: 3.860 95% (CI: 1.097–13.576)) were substantially linked to the development of anemia among adult HIV patients. Conclusion and Recommendation. This study showed that anemia is still a problem among HIV patients on HAART. The burden of anemia was found to be high among patients with advanced WHO clinical stages, having a BMI less than 18.5 kg/m2, TB/HIV coinfection, being on AZT-based ART regimens, and taking cotrimoxazole preventive therapy (CPT). Consequently, it is suggested that early preventative interventions, such as serial hemoglobin follow-up, iron supplementation, and education about dietary consumption, be undertaken targeting the aforementioned groups. In addition, the preferred first-line ART regimen as per the latest national and WHO guidelines is recommended, especially for the above groups.